Meaning, Networks and Practices. Perceptions of Corruption in the Local Governments of the Macrosouth Zone (Chile) (Revista Iberoamericana de Estudios Municipales, 2022)
This article aims to analyze corruption in municipalities of the Macro-South zone of Chile, identifying the meanings, networks and practices that make it up as a social phenomenon from the perception of a series of local actors. To accomplish this, a qualitative methodology was used. 159 interviews were conducted between 2017 and 2020 with municipal officials, local authorities, experts on corruption issues and actors (interest groups) linked to the municipality. The main results show that corruption is defined heterogeneously by municipal and private actors. In addition, the importance of personal ties and networks, in addition to trust and reciprocity, for the operation of this phenomenon is highlighted.
Keywords: Corruption; Local governments; Social ties; Formality